2021
DOI: 10.1002/ppap.202100008
|View full text |Cite
|
Sign up to set email alerts
|

On the transition of reaction pathway during microwave plasma gas‐phase synthesis of graphene nanosheets: From amorphous to highly crystalline structure

Abstract: Fourier‐transform infrared spectroscopy and proton‐transfer‐reaction–mass spectrometry are used in a complementary way to study gas‐phase processes during decomposition of ethanol in a microwave plasma torch. Decomposition products (C, C2 and simple hydrocarbons) reassemble into higher hydrocarbons and graphene nuclei and further grow into graphene nanosheets (GNS). Depending on microwave power, ethanol flow rate and molecular gas admixture, the material structure changes from amorphous to crystalline. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…The yield decrease could be understood in terms of the reverse hydrogenation process of C 2 H and C 2 molecules when more gasphase hydrocarbons are formed (figure 1) and the amount of solid-state product decreases. This result is in agreement with the yield decrease of FLG and the analysis of decomposition products of ethanol formed in our microwave plasma torch discharge [33]. Together with previously reported FLG synthesis from ethanol (C 2 H 5 OH) and its isomer, dimethyl ether (CH 3 OCH 3 ) by Dato et al [14], our results showed that the synthesis using alcohols with the same stoichiometry is independent of the precursor molecular arrangement.…”
Section: Synthesis Of Graphene Nanosheets From Higher Alcoholssupporting
confidence: 93%
See 1 more Smart Citation
“…The yield decrease could be understood in terms of the reverse hydrogenation process of C 2 H and C 2 molecules when more gasphase hydrocarbons are formed (figure 1) and the amount of solid-state product decreases. This result is in agreement with the yield decrease of FLG and the analysis of decomposition products of ethanol formed in our microwave plasma torch discharge [33]. Together with previously reported FLG synthesis from ethanol (C 2 H 5 OH) and its isomer, dimethyl ether (CH 3 OCH 3 ) by Dato et al [14], our results showed that the synthesis using alcohols with the same stoichiometry is independent of the precursor molecular arrangement.…”
Section: Synthesis Of Graphene Nanosheets From Higher Alcoholssupporting
confidence: 93%
“…Dato et al [32] used mass spectrometry to analyze hydrogen content of the FLG prepared by microwave plasma decomposition of ethanol and only 1 at% or less of hydrogen was detected in the investigated material. This value is not surprising as most of the hydrogen is contained in the volatile hydrocarbon species such as CH 4 , C 2 H 2 , C 2 H 4 [33], and H 2 formed during the synthesis and escapes the experimental reactor by exhaust line.…”
Section: Synthesis Of Graphene Nanosheets From Acetylenementioning
confidence: 94%
“…While the hydrogen species could be generated by the dehydration reactions of ethanol in the plasma. [ 16,28 ] Further, the dissociation of ethanol could be observed from the detected CH and H α species and from OH, H β , and O species, which are likely present but not clearly observed in the spectra obtained. The H α emission at the bulk liquid (Point 2: L) shows to be relatively more prominent compared to the H α emission observed at the gas phase (Point 1: G) and the immersed substrate (Point 3: S).…”
Section: Resultsmentioning
confidence: 98%
“…The theoretical yield of carbon, that is, 46.9% was calculated in the tea tree oil (chemical formula C 28 H 60 O 4 P 2 S 4 Zn). The breakdown of tea tree oil in the microwave plasma generated various carbon species, such as CO, CO 2 , and CH, [ 39 ] which contributed to ≈23% of the total yield of graphene.…”
Section: Resultsmentioning
confidence: 99%